The cybernetic constructivism as a metatheory of education: some contributions to the study and regulation of teaching and learning processes - Clara ROMERO PÉREZ (Ediciones Universidad de Salamanca, 2016)
This paper discusses the basic propositions from the constructivist theory and the second-order cybernetics to study the teaching and learning processes. As a metatheory, the cybernetic constructivism provides a new theoretical framework to analyse and better regulate the educational process with the aid of a new approaches. First, this article analyses the most representative metatheory ideas: cognition, self-awareness and structural fine-tuning in order to infer a new approach to rethink the educational praxis and to promote the pupil individual autonomy. In addition, we infer to the educational process a new pedagogical approach focused to the individual autonomy, the co-operation and the communication on the educational intra-system.